Edge stabilization in reduced-dimensional perovskites - Li Na Quan (Nature Portfolio, 2020)
Reduced-dimensional halide perovskites are promising for light-emitting diodes but suffer from photo-degradation. Here Quan et al. identify the edge of the perovskite nanoplatelets as the degradation channels and use phosphine oxides to passivate the edges and boost device performance and lifetime.